Sweet comeback or a rat-race for the ackee? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
It s only a yellow fruit, but it is almost sacred among its aficionadas, or ackee-onadas as they are coming to be known. The ackee is widely regarded as poisonous, yet it is the official national fruit of Jamaica, among whose diaspora it is...